Obesity-Driven Gut Microbiota Inflammatory Pathways to Metabolic Syndrome - Cavalcante-Silva, Luiz H. A.; Galvão, José G. F. M.; Silva, Juliane Santos de França da; Sales-Neto, José M. de; Rodrigues-Mascarenhas, Sandra (Frontiers in Physiology, 2015)
The intimate interplay between immune system, metabolism and gut microbiota plays an important role in controlling metabolic homeostasis and possible obesity development. Obesity involves impairment of immune response affecting both innate and adaptive immunity. The main factors involved in the relationship of obesity with inflammation have not been completely elucidated. On the other hand, gut microbiota, via innate immune receptors, has emerged as one of the key factors regulating events triggering acute inflammation associated with obesity and metabolic syndrome. Inflammatory disorders lead to several signalling transduction pathways activation, inflammatory cytokine, chemokine production and cell migration, which in turn cause metabolic dysfunction. Inflamed adipose tissue, with increased macrophages infiltration, is associated with impaired preadipocyte development and differentiation to mature adipose cells, leading to ectopic lipid accumulation and insulin resistance. This review focuses on the relationship between obesity and inflammation, which is essential to understand the pathological mechanisms governing metabolic syndrome.